2008
DOI: 10.1007/s11095-008-9798-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atorvastatin Versus Rosuvastatin on Levels of Serum Lipids, Inflammatory Markers and Adiponectin in Patients with Hypercholesterolemia

Abstract: Therapy with both statins not only significantly improved lipid profiles but also decreased levels of vascular biomarkers hs-CRP, MMP-9, and PAI-1; however, only rosuvastatin increased serum adiponectin levels significantly in patients with hypercholesterolemia, which could imply a beneficial effect in coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 45 publications
1
44
0
3
Order By: Relevance
“…Rosuvastatin, a lipid-lowering agent in clinical practice, has an appreciable anti-atherogenic property which is due to the improvement of endothelial dysfunction as well as its anti-thrombotic, anti-inflammatory and antioxidant effects (Qu et al, 2009;Rondi et al, 2014). Rosuvastatin has been reported to prevent MI induced experimentally by occlusion of left coronary artery in rats (Dourado et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Rosuvastatin, a lipid-lowering agent in clinical practice, has an appreciable anti-atherogenic property which is due to the improvement of endothelial dysfunction as well as its anti-thrombotic, anti-inflammatory and antioxidant effects (Qu et al, 2009;Rondi et al, 2014). Rosuvastatin has been reported to prevent MI induced experimentally by occlusion of left coronary artery in rats (Dourado et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Снижение уровня вч-СРБ соста-вило 40% и 34%, соответственно, (р=0,139). Анало-гичные результаты были показаны в ряде других исследований [24][25][26]. Таким образом, в большинстве сравнительных исследований во влиянии на вч-СРБ аторвастатин не уступал розувастатину, несмотря на более выраженный гиполипидемический эффект последнего.…”
Section: влияние на маркеры воспаленияunclassified
“…After being scanned, only eight studies were identified meeting the inclusion criteria and remained in the analyses [13][14][15][16][17][18][19][20] . Of the eight studies, four had routine-treatment groups [13][14][15][16] , which included no cholesterol-lowering drugs, two compared the effects of different doses of atorvastatin [17,18] , one compared the effect of atorvastatin versus rosuvastatin [19] , and one used healthy volunteers as a control group [20] . All eight articles could be used to evaluate the changes in serum levels of CRP and LDL-C from baseline to the end of follow-up, while only the four with routine-treatment groups could be used to compare the serum CRP and LDL-C levels after statin treatment with those after non-statin routine treatment [13][14][15][16] .…”
Section: Studies Identifiedmentioning
confidence: 99%
“…One study (12.5%) was from Hong Kong [17] , three (37.5%) from Taiwan [13,18,20] , and four (50%) from Mainland China [14][15][16]19] . Quality assessment, subject characteristics (such as the age, gender and clinical diagnosis), duration and dose of statin treatment of the included studies are shown in Table 1.…”
Section: Quality Assessment and Study Characteristicsmentioning
confidence: 99%